Administration of counterfeit sildenafil citrate to Wistar rats: impact on serum micronutrient levels - Iyanda, Ayobola; Oparinde, Dapo (International Journal of Biological Research, 2014)
Background: Counterfeit drugs have been recognized as a cause of many pathologic states, sometimes resulting in death. Even when their exposure does not lead to death, there is still the possibility of slight alteration in many physiologic processes in the body; namely digestion, absorption and homeostatic mechanisms. Objective: The objective of the study is to determine the impact of counterfeit sildenafil citrate on serum micronutrient levels in male Wistar rats. Method: Twenty-one rats (250 g) were randomly distributed equally into 3 groups. The first, second and third groups were administered with 25 mg/kg BW of fake sildenafil citrate, 25 mg/kg BW genuine sildenafil citrate and distilled water (control) respectively. The route of administration was by gastric gavage. The serum concentrations of trace elements and vitamins were estimated using the Atomic Absorption Spectrometry and High Performance Liquid Chromatography respectively. Statistical analysis of data was carried out by using analysis of variance. A p value of ? 0.05 was considered significant. Results: Results revealed that all the micronutrients were significantly different except thiamine, niacin, vitamin B12, Mn, Fe, Cr, Mo, Co, riboflavin, pyridoxine, pantothenic and vitamin D. All the animals survived till the end of the study. Conclusion: The implication of the results is that while fake drug exposure may not result in death, it may cause depletions in various micronutrients known for their vital roles in the body. Keywords: Fake Drug; Minerals; Vitamins; Sildenafil Citrate.